2022
DOI: 10.1093/jcag/gwac002
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Gastroenterology Career Pathway Experiences: Exploring the Gender Divide

Abstract: Background We aimed to determine the persistence of differential career experiences between male and female gastroenterologists in Canada >20 years after they were first noted in the literature. Methods A 51-question mixed-methods survey was developed focusing on personal, professional and financial characteristics. The survey was disseminated via email and fax to practicing gastroenterologists using provincial college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…These data were also confirmed by Arlow et al, who found that female trainees were more likely to choose skills according to family needs than males [ 20 ]. Women, significantly more than men (26% vs. 15%), must choose between their careers, marriage, or children [ 21 ]. However, women in gastroenterology fill an essential role that is irreplaceable and underappreciated.…”
Section: Discussionmentioning
confidence: 99%
“…These data were also confirmed by Arlow et al, who found that female trainees were more likely to choose skills according to family needs than males [ 20 ]. Women, significantly more than men (26% vs. 15%), must choose between their careers, marriage, or children [ 21 ]. However, women in gastroenterology fill an essential role that is irreplaceable and underappreciated.…”
Section: Discussionmentioning
confidence: 99%